Innovative decision-making on infrastructure and environment. Experiments with network management in the Netherlands - DRIESSEN, Peter P. J.; GLASBERGEN, Pieter (European Spatial Research and Policy, 2025)
This article elaborates on the proposition that to bring environmental aspects into the planning of large-scale public works in a responsible way, it is imperative to temper the emerging form of adversarial interaction, tuming it into a more collaborative form. To this end, it is necessary to develop a different organisation of the decision-making process. The strategy on which that process is based is called network management. In this article, two cases are presented in which network management has been applied in the Netherlands. One of these concerns the expansion of the Dutch national airport, Schiphol. The other case deals with the expansion of the port of Rotterdam. Finally, the experiences with network management are assessed from three perspectives.